"A Gunpowder-Smelling History Lecture"?—Learning at a Wild West History Theme Park. Issue 1 (2nd January 2021) - Svensson, Carl-Johan; Samuelsson, Tobias
Abstract: Lately, theme parks have emphasized the learning and edutainment aspects of their business. This has created new opportunities for theme parks and schools to cooperate. Research has shown that learning at science centers, a similar form of learning arena, tends to be out of context and that the learning outcomes are meager. High Chaparral, in southern Sweden, is a theme park primarily focusing on the American 1870s. With 160, 000–170, 000 visitors each year, the theme park is one of the largest arenas for history communication in Sweden, alongside traditional cultural heritage institutions. This paper presents an analysis of students, mainly aged 10–12 years, visiting the park. In the park, the children are presented with various fact- and skills-oriented activities. While the children enjoy the activities, they do not align the presentations with their school history education. Rather, the children relate them to their own everyday life experiences, and the idea of 1870s America they take from the park is, to a high degree, informed by popular TV and movie Westerns. While the theme park seems fun for the children, the findings of this analysis show that the park's theme is not easily connected to the Swedish history curriculum for the studied group of students. In particular, the park does not align with the constructivist ideals of the Swedish curriculum. This does not mean that learning possibilities are absent. The park contains multifaceted leaning opportunities, but given the park's present focus, these are not fully developed.